Online platform providing data on milk - Van Campenhout, Bjorn; Chamberlin, Jordan; Kariuki, S.; Ariong, Richard M. (CGIAR System Organization, 2024)
A website that aggregates and displays live data from milk samples taken in a random sample of milk collection center.